Increased phylogenetic resolution within the ecologically important Rhizopogon subgenus Amylopogon using 10 anonymous nuclear loci. (2nd January 2017) - Dowie, Nicholas J.; Grubisha, Lisa C.; Burton, Brent A.; Klooster, Matthew R.; Miller, Steven L.
ABSTRACT: Rhizopogon species are ecologically significant ectomycorrhizal fungi in conifer ecosystems. The importance of this system merits the development and utilization of a more robust set of molecular markers specifically designed to evaluate their evolutionary ecology. Anonymous nuclear loci (ANL) were developed for R . subgenus Amylopogon . Members of this subgenus occur throughout the United States and are exclusive fungal symbionts associated with Pterospora andromedea, a threatened mycoheterotrophic plant endemic to disjunct eastern and western regions of North America. Candidate ANL were developed from 454 shotgun pyrosequencing and assessed for positive amplification across targeted species, sequencing success, and recovery of phylogenetically informative sites. Ten ANL were successfully developed and were subsequently used to sequence representative taxa, herbaria holotype and paratype specimens in R . subgenus Amylopogon . Phylogenetic reconstructions were performed on individual and concatenated data sets by Bayesian inference and maximum likelihood methods. Phylogenetic analyses of these 10 ANL were compared with a phylogeny traditionally constructed using the universal fungal barcode nuc rDNA ITS1-5.8S-ITS2 region (ITS). The resulting ANL phylogeny was consistent with most of the species designations delineated by ITS. However, the ANL phylogeny provided much greater phylogenetic resolution, yielding new evidence for cryptic species within previously defined species of R . subgenus Amylopogon . Additionally, the rooted ANL phylogeny provided an alternate topology to the ITS phylogeny, which inferred a novel set of evolutionary relationships not identified in prior phylogenetic studies.